Analisis Tayangan Kartun Anak “Rabbids Invasion” Di Gtv Berdasarkan Tinjauan Dari Sudut Pandang Pedoman Perilaku Penyiaran Dan Standar Program Siaran (P3SPS) - Muhamad Hardandy Sutrisno; Siti Salmah Sarabiti; Cindy Meilany Putri (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
This study aims to identify and describe the children's cartoon show "Rabbids Invasion" on GTV through the point of view of the 2012 KPI Broadcasting Behavior Guidelines and Broadcasting Program Standards (P3SPS). The theories used in this research are broadcasting theory, program theory, child theory. -children, and the theory of P3SPS.This study uses a qualitative method by collecting information about the status of a symptom, namely the state of the symptoms according to what they were at the time the research was conducted. Data collection is done by observing and documenting. Data analysis was carried out by means of data reduction, data presentation and drawing conclusions.The results of this study indicate that there was an alleged violation of the children's cartoon program "Rabbids Invasion" on GTV on August 6 2019 when reviewed through P3SPS. The alleged offenses included assaulting a rabbit, dropping a bowling ball from top to bottom and hitting it on the head, throwing a cactus pot in the face with a racket and throwing a tart.The broadcast will have an impact on changing the attitudes and behavior of children who watch it, especially in terms of imitation and encourage youth to learn about inappropriate behavior and/or justify such inappropriate behavior as commonplace in everyday life. So Siarab programs in Indonesia must comply with the broadcasting law and P3SPS must be a guideline for/in making television program production so as to produce shows that are appropriate according to the existing classification, and are beneficial to the people of Indonesia.